Single-electrode triboelectric nanogenerator based on economical graphite coated paper for harvesting waste environmental energy. (December 2019) - Ankanahalli Shankaregowda, Smitha; Sagade Muktar Ahmed, Rumana Farheen; Nanjegowda, Chandrashekar Bananakere; Wang, Jingwei; Guan, Shirong; Puttaswamy, Madhusudan; Amini, Abbas; Zhang, Yulong; Kong, Dejun; Sannathammegowda, Krishnaveni; Wang, Fei; Cheng, Chun
Abstract: Single-electrode mode triboelectric nanogenerator (TENG), as an emerging and efficient sustainable power source, is highly sought to develop a low-cost fabrication process for the mass production at the commercial level. In this paper, we report an easy protocol for the fabrication of graphite coated paper (GCP) based electrode along with its application in highly flexible single electrode mode TENG for converting waste environmental energy to electricity. This GCP exhibits an excellent flexibility and hydrophobicity with sheet resistance of ~1.5 kΩ sq −1 . GCP-TENG is made up of polytetrafluoroethylene film tape, as the triboelectric layer, and GCP, as the conductive single electrode as well as its roll to roll fabrication was demonstrated. By efficiently harvesting hand tapping energy, GCP-TENG can generate a maximum open-circuit voltage up to ~320 V and a maximum short-circuit current density of ~0.8 μA cm −2, sufficient for charging capacitors and power Light-emitting diodes (LEDs) and Liquid crystal displays (LCDs) with rectifying circuits. We also demonstrated that GCP-TENG can efficiently work when adjoined with the skin of Pig leading to an effective harvesting of energy from the physical motion of animal. To indicate the universal usage of GCP-TENG, a wide range of common materials, such as paper, polyethylene terephthalate (PET), wood, polymethyl methacrylate (PMMA) and fabrics like cotton and nylon, concluded in effective electrical outputs when contacted with GCP-TENG. The widespread mechanical energy in nature associated with wind and water energy can be directly harvested by GCP-TENG, thus, it can be a promising sustainable tool for obtaining waste environmental energy from our daily activities, e.g., skin-touch actuated electronics, wearable/patchable self-powered sensory system, etc. Graphical abstract: Image 1 Highlights: Graphite coated paper (GCP) used as an electrode for TENG by a robust and convenient roll to roll process is proposed. This GCP electrode with excellent mechanical and electrical stability can replace expensive traditional metal electrodes. GCP-TENG is capable of harvesting waste mechanical energy from human body motion, animal motion, wind and water energy. The GCP-TENG possesses a moderate internal resistance of tens of MΩ with decent output power density up to 159 μW cm −2 .